The Impact of The Strengthened Gender Sensitive Midwifery Care on Pregnant Women's Knowledge, Attitude and Acceptance of Midwifery Care - Maryanah Maryanah; Indra Supradewi; Tut Barkinah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2021)
Background: Gender sensitive midwifery services are needed by women, especially during pregnancy, childbirth and puerperium. Gender inequality in society has a negative impact on the acceptance of antenatal care for mothers. Gender sensitive midwifery care is needed to improve maternal health status during pregnancy. Purpose: This study aims to determine the impact of gender sensitive midwifery care on pregnant women's knowledge, attitude and acceptance of midwifery care Method: This was a quantitative experimental study with pre-posttest for 1 group design. The subjects of this study were pregnant women who received midwifery care from 40 midwives, totaling 200 pregnant women obtained through purposive sampling in 2 provinces. Paired t-test was used to measure the difference in the results of the variables measured in pregnant women before and after 3 months of the intervention given by midwives. Results: Pregnant women's knowledge, attitude and acceptance of midwifery care increased after they received intervention from midwives. The mean difference (MD) for knowledge was -2.07 (r=0.864), p value=0.000 in DKI Jakarta, and MD=-2.70 (r=0.467), p value= 0.000 in South Kalimantan. For attitude in DKI Jakarta, MD=-1.03 (r= 0.99, p value=0.000) and in South Kalimantan the mean difference (MD) was -2.8 (r= 0.445, p value=0.000). For acceptance of gender sensitive midwifery care in DKI Jakarta MD=-2.71 (r= 0.67, p value= 0.000) and South Kalimantan MD=-4.5 (r= p value=0.000). Conclusion: There was a difference and increase in score for knowledge, attitude and acceptance of midwifery care with gender sensitivity in pregnant women before and after the intervention was given to the midwives in the two provinces. It takes great attention from midwives to ensure that all pregnant women receive a gender sensitive midwifery care.